Avaliação do perfil antiinflamatório e antinociceptivo da casca do caule de Aspidosperma tomentosum (Apocynaceae). - Aquino, Anansa Bezerra de (2010)
In this study we evaluated the antinociceptive and anti-inflammatory activities of the stem bark of the species Aspidosperma tomentosum in models of pain and inflammation induced in mice. A A. tomentosum belongs to the family Apocynaceae that has been extensively studied and characterized chemically by the frequent occurrence of alkaloids, some of therapeutic importance, such as vinblastine and vincristine. This species is known as pau-pereiro do campo and was collected in the Brazilian cerrado, in the city of Planaltina the state of Goiás, in May 2004. We assessed the antinociceptive and anti-inflammatory activity of crude ethanol extract obtained by extraction with 20 L of 90% ethanol, fractions obtained by chromatography adapted, according to a solvent gradient of increasing polarity, and the flavonoid isorhamnetin, obtained in the filtration of crude ethanolic extract of stem bark of A. tomentosum. We conducted the following tests: test of writhing induced by acetic acid, hot plate, formalin, ear edema induced by capsaicin, peritonitis induced by thioglycollate 3%. Was also evaluated motility and / or depression of the central nervous system by the test of catalepsy. For statistical analysis we used ANOVA followed by Dunnet test, the tutorial Prisma ®. Values were considered significant when * p <0.05, ** p <0.01 and *** p <0.001. The results were expressed as mean ± standard error of the mean. In the abdominal writhing test induced by acetic acid, ethanol extract and fractions showed higher inhibition between 50.8% to 59.7%, compared with dipyrone. In the hot plate test, the fractions Hex: CHCl3 50%, 100% CHCl3 and CHCl3: MeOH 5% showed an increase in latency of the animal on the hot plate, and this result was reversed in the presence of naloxone. In the test of nociception induced by formalin, the crude ethanol extract and its fractions presented significant results in both phases of testing, when compared to control, and the CHCl3 100% fraction presented better performance in both phases (average latency time of 61s and 75s the first and second phases, respectively). In the test of ear edema induced by capsaicin only the soluble fraction of crude ethanol extract, the fraction of CHCl3: MeOH 10% and isorhamnetin showed no inhibition of edema, where the CHCl3: AcOEt 50% was the most active (64.2% of inhibition of edema). In the trial of peritonitis the crude ethanol extract, the isorhamnetin and the fractions used inhibited cell migration, except the fraction AcOEt 100%. The test result of catalepsy suggests that treatment with the fractions Hex: CHCl3 50%, 100% CHCl3 and CHCl3: MeOH 5% of the isolated species A. tomentosum not alter the motor skills of the animal. The results observed in this study indicate that the species A. tomentosum is able to modulate the antinociceptive and antiinflammatory response.